2006
DOI: 10.4161/cc.5.6.2604
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulation of the Anaphase Promoting Complex in Human Cells by Cyclin A-Cdk2 and Cyclin A-Cdk1 Complexes

Abstract: We are grateful to Jiri Lukas (Danish Cancer Society, Denmark) for providing us with the wild type Cdh1-expressing U2-OS cell line and the Cdh1 mutant (RVL-AAA) plasmid. We thank Andrew Ippolito for editorial assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 22 publications
(39 reference statements)
1
25
0
2
Order By: Relevance
“…Since SFETP SLBP was expressed at normal levels during S phase and then degraded, we conclude that phosphorylation of Thr61 by cyclin A/Cdk1 is essential for proper timing of the degradation of SLBP. In support of this, it has been shown that cyclin A/Cdk1 is activated at the end of S phase (21,22). Thus, the mutagenesis data taken together with our biochemical results implicate cyclin A/Cdk1 as the kinase that phosphorylates Thr61 of SLBP, and this phosphorylation triggers degradation of SLBP at the end of S phase.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Since SFETP SLBP was expressed at normal levels during S phase and then degraded, we conclude that phosphorylation of Thr61 by cyclin A/Cdk1 is essential for proper timing of the degradation of SLBP. In support of this, it has been shown that cyclin A/Cdk1 is activated at the end of S phase (21,22). Thus, the mutagenesis data taken together with our biochemical results implicate cyclin A/Cdk1 as the kinase that phosphorylates Thr61 of SLBP, and this phosphorylation triggers degradation of SLBP at the end of S phase.…”
Section: Resultssupporting
confidence: 58%
“…Although there is high cyclin A/Cdk2 activity throughout S phase, both the in vitro Thr61 kinase activity in cell lysates and the SLBP degradation in vivo do not occur until the S/G 2 border. Thus, the Thr61 phosphorylation profile we detected correlates well with cyclin A/Cdk1 activity which increases toward late S phase, with a gradual increase toward the point where it peaks at G 2 (21,22).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We first asked whether endogenous Cdk2 and Wee1 are physically associated. Cdk2 is the major Cdk partner of cyclin A in human cells and does not bind appreciably to cyclin B in the presence of Cdk1 (21,35,37,38). Cdk2 was readily detected in somatic Wee1 immunoprecipitates (IPs) derived from asynchronous cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because Cdk2 binds most cyclin A present in U2-OS cells during late S and G 2 phases (37), most Wee1 bound to cyclin A is likely in complex with Cdk2. Some complexes may also contain Cdk1, which associates with a low but increasing fraction of cyclin A as U2-OS cells approach mitosis (38). (18).…”
Section: Resultsmentioning
confidence: 99%